BLOOD MONOCYTE SUBPOPULATIONS DURING UNCOMPLICATED CORONARY ARTERY BYPASS SURGERY - A. S. Golovkin (SPb RAACI, 2014)
Abstract. We have observed thirty-six patients with coronary artery disease (CAD) who have undergone coronary artery bypass graft (CABG) surgery. In patients with uncomplicated clinical course post-CABG, total lymphocyte counts, T-, B- and NK-cell contents did not significantly differ from baseline levels. Meanwhile, the numbers of CD14HIGH and CD14LOW monocyte subpopulations showed significant differences from initial levels at day 1 and day 7 after surgery. The changes in monocyte subsets in blood of patients with and absence of post-surgical septic complications reflected severity of inflammatory response, and development of systemic inflammatory syndrome. In such a case, further studies of peripheral blood monocytes can be both a useful tool for studying the mechanisms of systemic inflammation, as well as a good diagnostic system, in order to assess the patient’s condition and to predict post-surgical clinical outcomes.